The Process of Stakeholder Involvement in the Decarbonisation of the Northern Hungary Coal Region - Bujdosó, Zoltán; Bordás, Anikó; Hegyi, Balázs; Piskóti-Kovács, Zsuzsa; Vaszkó, Csaba; Nagy, Richárd; Kovács, Gyöngyi; Zörög, Zoltán (Acta Carolus Robertus, 2022)
This article deals with the analysis of Hungary's still existing coal region (Northern Hungary), including the future of coal mining and energy production. Within the interpretive tradition of social research, we approached the problem and explored the role and significance of the Mátra Power Plant in the country and in the coal region. The results show that there has been widespread involvement in the field of coal removal, Just Transition, and that it is important for decision-makers and energy policy stakeholders in the country and the region to have a say. It also helps to shape discourses and bring out alternative views.
Keywords: North Hungary; coal region; Just transition; stakeholder involvment